One-Year Outcomes of M-TEER With the PASCAL System in Atrial and Ventricular FMR: Insights From the MiCLASP Postmarket Clinical Follow-Up Study - Amir A. Mahabadi; Tienush Rassaf; Tobias Kister; Thomas Schmitz; Tobias Geisler; Edith Lubos; Jörg Hausleiter; Ingo Eitel; Ralph Stephen von Bardeleben; Sergio Berti; Axel Linke; Christian Hengstenberg; et al. (Circulation: Cardiovascular Interventions, 2026)
BACKGROUND: Studies on mitral transcatheter edge-to-edge repair for atrial functional mitral regurgitation (AFMR) and ventricular functional mitral regurgitation (VFMR) are limited. METHODS: We report 1-year outcomes of mitral transcatheter edge-to-edge repair for AFMR and VFMR using the PASCAL transcatheter valve repair system in the MiCLASP multicenter European postmarket clinical follow-up study (REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04430075). RESULTS: Analysis included 295 patients with functional mitral regurgitation (75.5±9.93 years old, 59.3% male) from the first 600 enrolled in the MiCLASP study, with AFMR in 17.6% (52) and VFMR in 82.4% (243). Patients with AFMR were older (79.7±6.67 versus 74.6±10.30 years), majority female (75.0% versus 33.3%), and had higher rates of hypertension (98.1% versus 82.3%) and atrial fibrillation (82.7% versus 60.1%) than patients with VFMR (all P